Research on the Supply Efficiency of Marine Ecological Products in the Yangtze River Delta Costal Urban Agglomerations Based on DEA-Tobit Model - He, Yixiong; Song, Weiming; Yang, Fan (Sustainability, 2021)
In this research, we choose the coastal cities in the Yangtze River Delta as the subjects of study, including Shanghai, Lianyungang, Yancheng, Nantong, Jiaxing, Ningbo, Zhoushan, Taizhou, and Wenzhou, nine cities in total. With marine ecological products as the starting point and the supply efficiency of marine ecological products in each city as the subjects of research, and after collecting a quantity of data and by constructing the efficiency analyzing modes, we analyze the supply efficiency of those cities with the involved supplying service, cultural service, and value of regulating service as the output, and the operation of related authorities as the input of marine ecological products. Meanwhile, combining with the outside factors affecting the supply efficiency, we explore and identify the existing problems of marine ecology products in this region, such as the unreasonable supply structure, regional development imbalance, marine environment quality degrading, etc., and present the corresponding solutions and rationalization proposal for the existing problems, thus providing a new thought for promoting the development of the Yangtze River Delta, especially for marine activities.